Cambios de uso del suelo e impactos sobre el agua subterránea en un barrio al sur de Tandil, Buenos Aires, Argentina - Ruiz de Galarreta, Alejandro (2012)
This work is based on land use changes since 2003 to 2011 in a peripheral sector of 75 hectares, located at the Southern hilly area of Tandil city, and its connection with groundwater quality and availability. Satellite images were mapping and contrasting through field work. It showed land use variations in the study area, changing from non defined lands uses and crop lands to tourist-commercial and residential utilization. However, this sector does not have drinkwater and sewer systems. People use domiciliary boreholes to exploit phreatic aquifer for human and recreational consumption and they spill their effluent in cesspits. Several problems related with groundwater use were detected, like as boreholes drying, need to make deeper boreholes, water quality disturbances, groundwater shortage in summer mainly for swimming pools, clogging of cesspits because of extreme rains. Phreatic levels were measured and groundwater samples were taken in 2011, in order to know electrical conductivity (EC) and nitrates. EC varied between 480 and 1400 μS/cm, showing local contamination in the more populated zone. Nitrates have the same behavior varying since 6 to 85 mg/L, including a site with more than 200 mg/L. These alterations are mainly caused by local disposition of domiciliary effluents generating a half-closed cycle of disposition-transport-groundwater exploitation. The lack of land planning considering environmental characters together with the absence of sanitary services and urbanization in a recharge zone generates a risk for quality and availability of groundwater and population health.